The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.5935/medicalexpress.2016.01.04
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an Educational Program on Schoolchildren’s Energy Expenditure during Physical Education Classes

Abstract: OBJECTIVE: Physical activity is a means of prevention of noncommunicable diseases. The level of physical activity of children is decreasing in Brazil, and this can increase the risks of diseases associated with sedentary lifestyles and obesity. METHOD: This is a school-based randomized controlled trial which evaluated the impact of an educational intervention on children's physical activity level, energy expenditure, and teacher's behavior during physical education classes at public schools in São Paulo. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 28 publications
1
10
0
4
Order By: Relevance
“…Physical education at school encompasses motor, cognitive, affective and social development of children and adolescents (Cunha, Poblacion, Colugnati, Taddei & Bracco, 2016). The current study found significant social selfconcept results in students belonging to the PE group.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…Physical education at school encompasses motor, cognitive, affective and social development of children and adolescents (Cunha, Poblacion, Colugnati, Taddei & Bracco, 2016). The current study found significant social selfconcept results in students belonging to the PE group.…”
Section: Discussionsupporting
confidence: 49%
“…All self-concept subscales (personal, school, family and social) showed higher frequency of moderate or high scores in both herein analyzed groups. Accordingly, Cunha et al (2016) pointed out that 7-11-year-old students had very good perception about themselves, since they presented high scores on personal, school, family and social self-concept. In light of the present study, and of the study conducted by Cunha et al (2016), it is possible assuming that students belonging to the age group 7-11 years show good self-perception, as well as that the aging factor has negative influence on self-concept perception (Serassuel Junior, Cavazzotto, Paludo, Zambrin & Simões, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previamente, da Cunha et al ( 2016) evidenció un mayor gasto energético en escolares cuyos profesores fueron intervenidos con educación teórico-práctica sobre actividad física (estrategias para mantener el movimiento durante la CEF) y nutrición orientados a la salud infantil, respecto al grupo de profesores no intervenidos (2.54 kcal/min contra vs 1.81 kcal/min, respectivamente) (da Cunha et al, 2016). En nuestro estudio, los grupos NP, SP y OB obtuvieron promedios de 1.36 kcal/min, 1.21 kcal/min y 1.25 kcal/min respectivamente, demostrando el bajo gasto energético conseguido durante la CEF.…”
Section: Niveles De Actividadunclassified
“…Sin embargo, algunos estudios han demostrado tiempos inefectivos de AFMV (Retamal-Valderrama, Delgado Floody, Espinoza-Silva, & Jerez-Mayorga, 2018) y limitado gasto energético (da Cunha, Poblacion, Basile, de Aguiar Carrazedo, & Maia, 2016) durante las CEF. Esto último, fue mayormente observado en niños que poseen valores elevados de IMC (da Cunha et al, 2016;Retamal-Valderrama et al, 2018). Lamentablemente, en la mayoría de estos estudios, la medición de la AFMV fue llevada a cabo con herramientas que tienen algún grado de subjetividad, ya que reúnen información desde la observación directa o cuestionarios.…”
Section: Introductionunclassified